Spatial Fluctuation of Regional Myocardial Blood Flows - Matsumoto, T.; Ebata, J.; Tsujioka, K.; Ogasawara, Y.; Kajiya, F. (Methods of Information in Medicine, 1997)
Digital radiography (100 pixels/mm2) combined with the technique of 3H-labeled desmethylimipramine deposition was employed to visualize regional blood flow distributions in rabbit left ventricular myocardium. A fluctuated pattern of myocardial flow and its dependence on arterial oxygen tension (PaO2) was evaluated with the coefficient of variation (CV) computed at each step of coarse-graining; flow images were revisualized by increasing pixel area (PA) step by step from 0.01 to 1 mm2. The CV values decreased with hypoxia at all resolution levels, suggesting that there is a vascular regulatory mechanism for making myocardial perfusion uniform in response to decreased PaO2. In both perfusion states, Cl/decreased with increasing PA. The relationship between CV and PA fitted the noninteger power law function, implying an apparent fractality of CV.
Keywords: Radioactive Molecular Flow Marker; Hypoxia; Vasoregulation; Fractal